Shuttling Tolerogenic Dendritic Cells across the Blood–Brain Barrier In Vitro via the Introduction of De Novo C–C Chemokine Receptor 5 Expression Using Messenger RNA Electroporation - Maxime De Laere; Judith Derdelinckx; Judith Derdelinckx; Mari Hassi; Mari Kerosalo; Heidi Oravamäki; Johan Van den Bergh; Zwi Berneman; Zwi Berneman; Nathalie Cools (Frontiers in Immunology, 2018)
The use of tolerance-inducing dendritic cells (tolDCs) has been proven to be safe and well tolerated in the treatment of autoimmune diseases. Nevertheless, several challenges remain, including finding ways to facilitate the migration of cell therapeutic products to lymph nodes, and the site of inflammation. In the treatment of neuroinflammatory diseases, such as multiple sclerosis (MS), the blood–brain barrier (BBB) represents a major obstacle to the delivery of therapeutic agents to the inflamed central nervous system (CNS). As it was previously demonstrated that C–C chemokine receptor 5 (CCR5) may be involved in inflammatory migration of DCs, the aim of this study was to investigate CCR5-driven migration of tolDCs. Only a minority of in vitro generated vitamin D3 (vitD3)-treated tolDCs expressed the inflammatory chemokine receptor CCR5. Thus, messenger RNA (mRNA) encoding CCR5 was introduced by means of electroporation (EP). After mRNA EP, tolDCs transiently displayed increased levels of CCR5 protein expression. Accordingly, the capacity of mRNA electroporated tolDCs to transmigrate toward a chemokine gradient in an in vitro model of the BBB improved significantly. Neither the tolerogenic phenotype nor the T cell-stimulatory function of tolDCs was affected by mRNA EP. EP of tolDCs with mRNA encoding CCR5 enabled these cells to migrate to inflammatory sites. The approach used herein has important implications for the treatment of MS. Using this approach, tolDCs actively shuttle across the BBB, allowing in situ down-modulation of autoimmune responses in the CNS.